2022
DOI: 10.1161/circoutcomes.122.008951
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Effectiveness and Safety of Direct Oral Anticoagulants Versus Warfarin Among Adults With Cancer and Atrial Fibrillation

Abstract: BACKGROUND: While clinical guidelines recommend direct-acting oral anticoagulants (DOAC) over warfarin to treat isolated nonvalvular atrial fibrillation, guidelines are silent regarding nonvalvular atrial fibrillation treatment among individuals with cancer, reflecting the paucity of evidence in this setting. We quantified relative risk of ischemic stroke or systemic embolism and major bleeding (primary outcomes), and all-cause and cardiovascular death (secondary outcomes) among older individuals w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…According to a Surveillance, Epidemiology, and End Results cancer registry database analysis, similar risks of stroke, systemic embolism, and severe bleeding have been observed in older persons with cancer and AF who were exposed to NOACs or warfarin. In comparison to warfarin, NOAC use was linked to a decreased risk of death from all causes and a similar risk of cardiovascular death [61].…”
Section: S-stroke Historymentioning
confidence: 99%
“…According to a Surveillance, Epidemiology, and End Results cancer registry database analysis, similar risks of stroke, systemic embolism, and severe bleeding have been observed in older persons with cancer and AF who were exposed to NOACs or warfarin. In comparison to warfarin, NOAC use was linked to a decreased risk of death from all causes and a similar risk of cardiovascular death [61].…”
Section: S-stroke Historymentioning
confidence: 99%
“…Nonvitamin K oral anticoagulants (NOACs) are innovative agents generated in a cascade by thrombin inhibitors or direct factor Xa inhibitors. Numerous studies have shown that NOACs are effective in both the prevention and treatment of venous thromboembolism 1 6 . NOACs are gaining popularity because of their rapid onset and offset of action, predictable pharmacodynamics that reduce the need for routine therapeutic monitoring, and fewer dietary or drug interactions in comparison to warfarin 7 .…”
Section: Introductionmentioning
confidence: 99%